Adaptive governance in the water-energy-food-ecosystem nexus for sustainable community sanitation - Evi Siti Sofiyah; Imelda Masni Juniaty Sianipar; Ari Rahman; Naila Putri Caesarina; Sapta Suhardono; I Wayan Koko Suryawan; Chun-Hung Lee (World Development Sustainability)
As the intensity of global environmental challenges increases, so does the need to understand and strengthen the resilience of interconnected systems. This research underscores the crucial role of adaptive governance in navigating the complexities of the Water-Energy-Food-Ecosystem nexus, particularly under the pressures of changing climatic conditions. The study conducts an in-depth analysis of adaptive capacities by identifying critical components such as assets, flexibility, organization, learning, and agency as fundamental elements of adaptive governance in sanitation practices. Data were collected through structured questionnaires and analyzed using binary probit and logit models to examine how these attributes influence community engagement in sanitation. Descriptive analysis was also used to summarize respondent characteristics and attribute distributions.